Rate of Binding of Antibiotics to Canine Serum Protein - Waterman, N. (1974)
The time rates of binding of three antibiotics of similar chemical structure, each with differing degrees of protein binding, were determined. Cephaloridine, which is 10% bound by serum proteins, was bound at a more rapid rate than cephalothin, which is 40% bound by serum protein. Cefazolin, bound 80%, required for longest time period for maximum binding to occur. The rate of protein binding appears directly related to the total percentage bound. The data from this study indicate that prolonged rates of binding of highly protein-bound drugs may influence pharmacological studies.